Digital forensics with open source tools - Altheide, Cory; Carvey, Harlan (Burlington, MA : Syngress, 2011)
Based on the use of open source tools, this book lends itself to many organizations as well as students who do not have means to purchase new tools for different investigations. Well known forensic methods are demonstrated using open-source computer forensic tools (Sleuthkit, Foremost, dcdd, pyag, etc.) for examining a wide range of target systems (Windows, Mac, Linux, Unix, etc.). The digital forensics industry is growing a rapid pace and this book is perfect for someone entering the field that does not have access to corporate tools. Written by world-renowned forensic practitioners Covers open source forensics tools for all major systems: Windows, Mac, and Linux Uses the most current examination and analysis techniques in the field.
Digital forensics with open source tools -- The open source examination platform -- Disk & file system analysis -- Windows systems and artifacts -- Linux systems & artifacts -- Mac OS X systems & artifacts -- Internet artifacts -- File analysis -- Automating analysis & extending capabilities.
Includes bibliographical references.
Keywords: COMPUTER CRIMES -- INVESTIGATION